Comparative assessment of economically valuable traits of semi-coarse hair and coarse-hair sheep in Republic of Tuva - S. S. Mongush (Аграрная наука Евро-Северо-Востока, 2021)
In Republic of Tuva sheep breeding is a leading branch of animal husbandry. According to the Ministry of Agriculture and Food, the number of sheep is 980 thousand heads at the 1st of January 2021. Among them the percentage of Tuva-Saraja coarse-hair hybrids is more than 60%. The purpose of the work is to study economically valuable traits of Tuva-Saraja sheep of a new type in comparison with Tuva coarse-hair short-fat tailed sheep. For comparative assessment of live weight, dirty wool clip and length of wool according to the method of random sample, out of the herd there were selected 30 heads of ram lambs yearlings and 30 heads of ewe lambs yearlings of Tuva-Saraja semi-coarse-hair sheep of new type and Tuva coarse-hair short-fat tailed sheep. The results of research have shown, that rams and ewes yearlings of Tuva-Saraja semi-coarse-hair breed of new type significantly differ in size and wool productivity. They predominate over the lambs of the same age of Tuva coarse-hair short-fat tailed in live weight by 3.2-3.4 kg (9,7-10.2 %) statistically more, than Tuva coarse-hair short-fat tailed of the same age. The longest wool was recorded in rams yearlings of new type, with underwool of 7.8 cm that exceeded the length of underwool of Tuva ram lambs yearlings by 1.3 cm or 20.0 %, the top hair was 14.4 cm and exceeded the same index in analogues by 3,4 cm or 30.9 %. Tuva coarse-hair ewe lambs yearlings gave way to the semi-coarse-hair ewes of new type in the length of underwool and top hair. Thus, the rams and ewes yearlings semi-coarse-hair ewes of new type considerably differ in live weight, dirty wool clip and length of wool in comparison with Tuva coarse-hair short-fat tailed of the same age.